1876 Ky. Acts 450, An Act to Amend an Act Entitled “An Act to Amend and Reduce into One Several Acts in Regard to the Town of Vanceburg, in Lewis County”§ 43 (Vol. II). - (:unkn) unknown (General Publisher, 1875)
No person, except watchmen, gunsmiths and militiamen in the discharge of their duty, or unless in defense of life or property, shall fire a gun or pistol within the city limits: any person thus offending shall be fined not less than one dollar nor more than five dollars.
--
Keywords: DISCHARGE